Talent Management Application Model In Village Apparatus In Tegal Regency - Diryo Suparto; Eko Eddya Supriyanto (CV. Ridwan Publisher, 2020)
Talent management in public organizations has not been widely adopted compared to business organizations. This paper uses qualitative research that examines participant perspectives with interactive and flexible strategies. The focus of this research is the implementation of talent management in the village apparatus by emphasizing talent identification, talent development, and maintaining the talents of the village apparatus. The first step in implementing talent management is to map employees. This employee mapping aims to determine employees who are included in the talent to be included in the talent pool. The measurement of these two dimensions uses existing tools or instruments. Performance measurement uses the work performance assessment of village officials but can also use performance measurement.